PREDICTION OF HORIZONTAL GENE TRANSFER OF LACCASE GENE; A COMPARATIVE STUDY OF 30 PROKARYOTIC GENOMES - TRIPTI SHARMA (The Bioscan, 2014)
Horizontal Gene Transfer (HGT) plays an important role in microbial evolution. Present study provides an in silico evidence for horizontal gene transfer of laccase gene. Laccases are multi- copper oxidases widely distributed among plants, fungi and bacteria, These enzymes are responsible for oxidation of a wide variety of organic and inorganic substrates and can be used for degradation of micropollutants in wastewater In the present paper computational methods were applied across 30 completely sequenced Laccase producing bacterial genomes of different subtypes of E coli, Salmonella, Serrantia, Psuedomonas,Bacillus and Vibrio for studying the prospects of horizontal gene transfer of Laccase Gene. Genome sequences, Laccase gene sequences and 16sr RNA sequences were retrieved from Kyoto Encyclopedia of Genes and Genomes. Genome and Laccase gene sequences were further analyzed and compared for their % GC content. Multiple sequence alignment was done and phylogenetic trees were constructed from 16 sr RNA and Laccase gene sequences using Mega-6. Differing patterns of 16S rRNA gene tree and the Laccase gene tree supported by high bootstrap values and discrepancies in %GC content of complete genome and of Laccase gene led to the conclusion that Horizontal Gene Transfer events might have taken place during the evolution of this gene.